Invoice and Payment Tracking System (IPMS) / Ainna Amirah Hissham Rizal - Hissham Rizal, Ainna Amirah (2018)
The project started by identifying the client business process, followed by identifying the problem faced by using the current business process. After several discussions with the client, they have stated what is the core requirement needed by their business process. The project then begins by declaring the objectives that need to be achieved. At this stage, the scope and method used to develop the project is also being identified. The development of the project is being done by using the Waterfall methodology. Throughout the development, evaluations from the user and expert are also being conducted to ensure that the system has been constructed according to the business requirements. Moreover, the comments and suggestion gained from the evaluation are also noted in order to make the necessary changes to the system. For the future enhancement, a few aspects such as interface, navigation, and process of purchasing can still be improved to provide more efficiency to the user.